Problematic issues connected to teaching Past Simple tense at elementary level - Skřivánková, Renata (2006)
This thesis deals with problems connected to teaching the Past Simple tense at elementary level. Theoretical part is followed by a description of research that I have conducted in connection with this work. I concentrated on problematic issues which occur in the textbook Inside Out Elementary. To find out more information I interviewed four teachers, and distributed questionnaires among teachers as well as students. The obtained data, which is included in the form of tables and graphs, helped me to specify the problems and suggest solutions.